2009
DOI: 10.1007/s10265-009-0232-x
|View full text |Cite
|
Sign up to set email alerts
|

Syncyte formation in the microsporangium of Chrysanthemum (Asteraceae): a pathway to infraspecific polyploidy

Abstract: Polyploidy, which is thought to have played an important role in plant evolution and speciation, is prevalent in Chrysanthemum (x = 9). In fact, polyploid series are known in C. zawadskii (2x, 4x, 6x, 8x, and 10x) and C. indicum (2x, 4x, and 6x), but the mechanism by which polyploidization occurs is unknown. Here we show that in diploid individuals of both C. zawadskii and C. indicum, the fusion between two adjacent pollen mother cells (PMCs) occurs at a frequency of 1.1-1.3% early in the first meiotic divisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 37 publications
5
44
0
Order By: Relevance
“…The pollen grains having 1.25-1.5 times the linear dimensions of haploid or n pollen grains are classified here as 2n (unreduced) pollen grains as has been suggested earlier (Darlington 1937, Ortiz 1997, Oselebe et al 2010, Xue et al 2011. As the 2n pollen grains are apparently fertile, there is every possibility that such 2n (unreduced) gametes can produce intraspecific polyploids as has been advocated earlier by many researchers in different plants (Falistocco et al 1995, Ortiz 1997, Kim et al 2009, Kumar and Singhal 2011a, 2011b, Singhal et al 2011a. Such 2n (unreduced) pollen grains with somatic chromosome numbers are considered to be the main driving forces for the natural polyploidization of plants.…”
Section: Discussionmentioning
confidence: 79%
“…The pollen grains having 1.25-1.5 times the linear dimensions of haploid or n pollen grains are classified here as 2n (unreduced) pollen grains as has been suggested earlier (Darlington 1937, Ortiz 1997, Oselebe et al 2010, Xue et al 2011. As the 2n pollen grains are apparently fertile, there is every possibility that such 2n (unreduced) gametes can produce intraspecific polyploids as has been advocated earlier by many researchers in different plants (Falistocco et al 1995, Ortiz 1997, Kim et al 2009, Kumar and Singhal 2011a, 2011b, Singhal et al 2011a. Such 2n (unreduced) pollen grains with somatic chromosome numbers are considered to be the main driving forces for the natural polyploidization of plants.…”
Section: Discussionmentioning
confidence: 79%
“…Some of the recent reports of cytomixis prevalent in plants from India include that of Lattoo et al (2006), Singhal et al (2007) and Singhal and Kumar (2008). According to some of the workers like Levan (1941), Zheng et al (1987), Ghanima and Talaat (2003) and Kim et al (2009), cytomixis plays a major role in chromosomal diversity and speciation of taxa. As per Bhat et al (2006), the extra chromatin mass received by one PMC from other during cytomixis can also form micronuclei or micro pollen in the later stages.…”
Section: Resultsmentioning
confidence: 99%
“…Cytomixis is thought to be caused by genetic/environmental factors or their associations (for review, see : Narain 1976, Baptista-Giacomelli et al 2000, Ghanima and Talaat 2003, Haroun et al 2004. Cytomixis plays a vital role in chromosomal diversity, as it forms hypo-/hyperploid cells and gametes afterward (Levan 1941, Zheng et al 1987, Kim et al 2009, and seemingly results are observed in the presently investigated populations. B-chromosomes are dispensable supernumerary chromosomes (in plants, firstly observed in rye and maize by Gotoh (1924) and Kuwada (1925), respectively), which do not recombine with the A-chromosomes and follow their own evolutionary pathway (Jones and Houben 2003).…”
Section: Meiotic Abnormalitiesmentioning
confidence: 86%